Psychiatric disorders, developmental, and academic difficulties among children and adolescents at-risk for schizophrenia: a controlled study - Funda Gumustas; Emel Koyuncu Kutuk; Yasemin Yulaf; Behice Han Almis (Psychiatry and Clinical Psychopharmacology, 2018)
OBJECTIVE: The aim of this study was to determine whether there are differences in the presence of developmental delays, academic difficulties, and current mental disorders between offspring of parents with schizophrenia (High risk: HR) and offspring of parents with no mental illness (control group) up to the age of 16 years. The relationship of existing differences with psychosocial difficulties of having a parent with schizophrenia was evaluated. METHOD: The sample of the study consisted of 35 HR and 30 control offspring aged 7–16 years. All parents were assessed using the SCID-I by a psychiatrist and offspring using the K-SADS-PL by a child psychiatrist. Information about the early developmental stages and academic difficulties of children were obtained through interviews with healthy parents. Emotional and behavioural problem levels of children were determined by the Strengths and Difficulties Questionnaire (SDQ), Swanson, Nolan, and Pelham-IV Questionnaire (SNAP-IV), the Screen for Child Anxiety Related Emotional Disorders (SCARED), and the Child Depression Inventory (CDI). All assessments were adjusted for socio-demographic variables. RESULTS: The rates of generalized anxiety disorders, delayed walking, delayed speech and reading difficulties, the levels of conduct problems (CP), depression, and school phobia were significantly higher in HR offspring than in control. When adjusted for socio-demographic variables, the presence of delayed speech and reading difficulties and only CP levels continued to be significantly higher in HR group (p < .05). These differences were not associated with gender of ill parent, duration of parental illness, and hospitalization in affected group (p > .05). CONCLUSION: Internalizing problems such as anxiety and depression are considered as a psychosocial result of having a schizophrenic parent. The higher rates of speech delay, reading difficulties, and CP level might be genetically associated with schizophrenia.